HADIS TENTANG SEBAIK-BAIK MANUSIA - Natsir, M. Iqbal; Ahmad, La Ode Ismail (Program Pascasarjana, UIN Alauddin Makassar, 2019)
There is a hadith about the virtue of people who study the Qur'an and teach it in some sources of trusted hadith. To analyze the hadith and explore the benefits of the hadith, it is very interesting to study and studied. In this study used the method maudu’i or a thematic study by collecting some hadith related to the theme of the good human is the study of the Qur'an and teach it. And the type of research used is qualitative research. Qualitative research is used with the intention that this research be obtained from the research results by using natural means so that the data obtained far from the rules or the subjective nature of the researcher or the author's tendencies in Do this research. In this study is examined about the quality of hadith as good as human beings is who study the Qur'an and teach it and the virtue of the people who study the Qur'an and teach it. In studying the Qur'an should be considered both aspects of studying the Qur'an in accordance with the rules of reading the Qur'an, and the second is to understand the meaning of the Qur'an and its subsequent laws to be made into life And make it a living guideline to get the world and the hereafter.